Efficacy of the trans‑obturator and retropubic mid‑urethral slings for stress urinary incontinence - Matej Keršič; Maruša Keršič; Tina Kunič; Matija Barbič; Ivan Verdenik; David Lukanović; Adolf Lukanović (Zdravniški Vestnik, 2019)
Background: The aim of our study was to report the extended long-term results of the use of tension-free vaginal tape (TVT) and trans-obturator tape (TOT) for the treatment of female urinary stress incontinence (SUI) at the Division of Gynaecology and Obstetrics / UMC Ljubljana. There are few data on this topic in the literature. Our aim was to find out whether and how the procedure improved the patients’ quality of life and for how long, whether the patients had complications after the procedure, and how this type of procedure affected the long-term results. Methods: A retrospective clinical trial comparing the use of TVT and TOT was carried out from January to August 2017 and included all the patients operated on at the Division of Gynaecology and Obstetrics / UMC Ljubljana with TVT or TOT procedure for stress or mixed urinary incontinence (UI) associated with urethral hyper mobility (the stress component was clinically predominant). The exclusion criteria were more than 10 years from procedure, age more than 80 years in 2016, previous anti-incontinence surgery and/or pelvic organ prolapse more than stage I on POP–q in any vaginal compartment. After inclusion and exclusion criteria, 1104 patients were sent quality-of-life questionnaires (PGI-S, PGI-I, SANDVIK SEVERITY SCALE, UDI-6, IIQ-7, ICIQ-UI Short Form (Slovenian)) with questions about the diagnosis, procedures, complications, reoperations, post-operative results, and satisfaction with the procedure. Till August 2017 (6 months after sending) we received 466 questionnaires (42.2 % response rate). After 225 questionnaires were excluded due to incomplete data, 241 questionnaires were analysed. Results: In the analysed group of patients (N = 241), 189 (78 %) had TOT and 52 (22 %) had TVT. Our retrospective study has confirmed that the efficacy and safety of TOT and TVT in the surgical treatment of SUI are comparable. The TOT and TVT groups did not differ significantly from each other in PGI-S, PGI-I, SANDVIK SEVERITY SCALE, UDI-6, IIQ-7, and ICIQ-UI Short Form or in postoperative complication rate. Repeat surgery was needed in 25/189 (13.2 %) TOT patients and 12/52 (23.1 %) TVT patients; p = 0.082. Urinary retention appeared in 18/189 (9.5 %) TOT patients and 7/52 (13.5 %) TVT patients; p = 0.411. Mesh erosion/inflammation appeared in 12/189 (6.3 %) TOT patients and 2/52 (38 %) TVT patients; p = 0495. Conclusion: We can conclude that the efficacy and safety of TOT and TVT in the surgical treatment of SUI are comparable. The choice of the technique should be based on the relative pros and cons of techniques and the surgeon’s experience.